FUNGSI INTERMEDIASI LEMBAGA KEUANGAN PERDESAAN DALAM MENDUKUNG PEMBIAYAAN PERTANIAN DI JAWA BARAT - Tuti Karyani (Universitas Padjadjaran, 2012)
Nowadays there are various rural financial institutions (RFI), but unfortunately farmers and agribusiness SMEs are still face lackof capital. In general, risk averse attitudes among RFIs upon agricultural and rural sectors were still dominant, so intermediaryfunction of RFI was not running well. The research was conducted in West Java with at macro level using panel regression analysis and at micro level using the SEM. The results at the macro level show that RFI intermediation function was affected by DPK, NPL and the SBI. Amount of credit disburse reduce poverty level. So that poverty in West Java was difficult to be reduce as long as intermediary role of RFI was not well function. On the micro level the intermediary function reflected on the quality of service which turns a positive effect on business performance and sustainability of farmers and agribusiness SMEs.